Detection of Borrelia burgdorferi Cell-free DNA in Human Plasma Samples for Improved Diagnosis of Early Lyme Borreliosis. (25th June 2020) - Branda, John A; Lemieux, Jacob E; Blair, Lily; Ahmed, Asim A; Hong, David K; Bercovici, Sivan; Blauwkamp, Timothy A; Hollemon, Desiree; Ho, Carine; Strle, Klemen; Damle, Nitin S; Lepore, Timothy J; et al.
Abstract: Background: Laboratory confirmation of early Lyme borreliosis (LB) is challenging. Serology is insensitive during the first days to weeks of infection, and blood polymerase chain reaction (PCR) offers similarly poor performance. Here, we demonstrate that detection of Borrelia burgdorferi ( B.b. ) cell-free DNA (cfDNA) in plasma can improve diagnosis of early LB. Methods: B.b. detection in plasma samples using unbiased metagenomic cfDNA sequencing performed by a commercial laboratory (Karius Inc) was compared with serology and blood PCR in 40 patients with physician-diagnosed erythema migrans (EM), 28 of whom were confirmed to have LB by skin biopsy culture (n = 18), seroconversion (n = 2), or both (n = 8). B.b. sequence analysis was performed using investigational detection thresholds, different from Karius' clinical test. Results: B.b. cfDNA was detected in 18 of 28 patients (64%) with laboratory-confirmed EM. In comparison, sensitivity of acute-phase serology using modified 2-tiered testing (MTTT) was 50% ( P = .45); sensitivity of blood PCR was 7% ( P = .0002). Combining B.b. cfDNA detection and MTTT increased diagnostic sensitivity to 86%, significantly higher than either approach alone ( P ≤ .04). B.b. cfDNA sequences matched precisely with strain-specific sequence generated from the same individual's cultured B.b. isolate. B.b. cfDNA was not observed at any level in plasma from 684 asymptomatic ambulatory individuals. Among 3000 hospitalized patients tested as part of clinical care, B.b. cfDNA was detected in only 2 individuals, both of whom had clinical presentations consistent with LB. Conclusions: This is the first report of B.b. cfDNA detection in early LB and a demonstration of potential diagnostic utility. The combination of B.b. cfDNA detection and acute-phase MTTT improves clinical sensitivity for diagnosis of early LB. Abstract : Cell-free DNA derived from B. burgdorferi was detected in 64% of plasma samples from patients with laboratory-confirmed erythema migrans using next-generation sequencing. Combining this technique with acute-phase modified 2-tiered serologic testing resulted in 86% diagnostic sensitivity and 100% specificity.